2020
DOI: 10.1177/0886260520926314
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Trauma Exposure: Discrimination and Posttraumatic Stress, Internalizing, and Externalizing Problems Among Detained Youth

Abstract: According to the race-based traumatic stress model, racial discrimination is proposed to comprise a traumatic experience that results in posttraumatic stress symptoms, as well as internalizing and externalizing problems among youth. Accordingly, a significant body of research has emerged that supports the associations among these constructs. However, the majority of these empirical studies have not accounted for the potential role of traditionally defined traumatic events in these associations. This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
(66 reference statements)
1
10
0
Order By: Relevance
“…Although previous research has demonstrated that racial discrimination is associated with externalizing behaviors above those stemming from other psychosocial traumatic experiences among youth (Mendez et al, 2020), this study was among the first to demonstrate that similar associations exist in the context of internalizing concerns. Negotiating racial discrimination is a developmental process that necessitates sophisticated behavioral and cognitive coping strategies.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Although previous research has demonstrated that racial discrimination is associated with externalizing behaviors above those stemming from other psychosocial traumatic experiences among youth (Mendez et al, 2020), this study was among the first to demonstrate that similar associations exist in the context of internalizing concerns. Negotiating racial discrimination is a developmental process that necessitates sophisticated behavioral and cognitive coping strategies.…”
Section: Discussionmentioning
confidence: 50%
“…Among youth in particular, experiences of racial discrimination have been associated with acute and long‐lasting mental and behavioral health problems that can persist into adulthood (Assari et al., 2017). Indeed, even after controlling for “conventional” forms of childhood adversity, such as abuse and exposure to domestic violence, racial discrimination has been shown to continue to predict negative psychological trauma sequelae (Mendez et al., 2020). Alarmingly, Black adolescents report an average of five encounters of racial discrimination per day (English et al., 2020), which positions them to be particularly susceptible to experiencing trauma‐related mental health concerns.…”
Section: Conceptualizing Racial Discrimination As An Acementioning
confidence: 99%
“…Acquiring an understanding on the effect of culture can help the evaluator appreciate an examinee’s willingness or not to disclose psychological difficulties (Javier & Lamela, 2020). Considering culture also means attending to the effects of discrimination, marginalization, and intergenerational trauma (Griffith, 1998; Griffith & Dudley, 2020; Kerig et al, 2020; Mendez et al, 2020).…”
Section: Applying Trauma-informed Principles To Forensic Mental Healt...mentioning
confidence: 99%
“…Moreover, rejection sensitivity was found to predict a decrease in level of social support (Zielinski & Veilleux, 2014 ). Interestingly, trauma exposure can also increase aggression individuals with high rejection sensitivity, which may hinder their ability to seek support (Mendez, Mozley, & Kerig, 2020 ) although research in this area is still very limited. Taken together, rejection sensitivity has a negative impact on social support and hence it could affect recovery from trauma and facilitate PTSD but to date the association between PTSD and rejection sensitivity has not been investigated.…”
Section: The Role Of Rejection Sensitivitymentioning
confidence: 99%